"Erasing a mural does not erase reality": Queer visibility, urban policing, and the double life of a mural in Ecuador. (June 2022) - Morrison, Chandra
Halted by the police, repeatedly defaced, and ultimately erased, the mural El Amor No Tiene Género (Love Has No Gender) lasted less than one week on the streets of Quito before it disappeared under a layer of whitewash in July 2019. The image – a trio of kissing couples – was painted by local street artist Apitatán to celebrate Ecuador's landmark approval of marriage equality. Its destruction inspired widespread media coverage, direct-action activism, and institutional support for the mural which culminated in its revival two months later. This article investigates what the double life of Apitatán's mural reveals about the politics of visibility in Quito at a critical moment of consolidating political rights for the country's LGBTQ community. Drawing on digital ethnography and storytelling methods, I weave together these two visibility disputes – about the mural and about queer love – to illustrate how public visibility is always contingent. To do so, my analysis explores the interplay between erasure and policing practices to enforce conditions of visibility within the urban environment.